Soluble TREM2 is a potential biomarker for the severity of primary angiitis of the CNS - Guo, Tianshu; Ma, Jia; Sun, Jiali; Xu, Wangshu; Cong, Hengri; Wei, Yuzhen; Ma, Yuetao; Dong, Qiaoxi; Kou, Yunting; Yin, Linlin; Zhang, Xinghu; Chang, Haoxiao; et al. (Frontiers in Immunology, 2022)
Background: Primary angiitis of the central nervous system (PACNS) is a severe inflammatory disease, and soluble triggering receptor expressed on myeloid cells 2 (sTREM2) has been reported to be associated with inflammation of the CNS. However, the role of sTREM2 in PACNS remains unknown. Methods: We obtained serum and cerebrospinal fluid (CSF) samples from 18 patients diagnosed with PACNS, as well as 14 patients diagnosed with other neurological disorders with no evidence of inflammation. sTREM2 concentrations in the samples were detected by enzyme-linked immunosorbent assay. Levels of inflammatory cytokines, including tumor necrosis factor-α, interleukin (IL)-6, IL-8, IL-1β, and complement C4, also were tested. The modified Rankin scale (mRS), National Institutes of Health Stroke Scale (NIHSS), and activities of daily living (ADL) scores were obtained as indicators of disease severity. In PACNS patients, cerebral lesion volume was evaluated by magnetic resonance imaging. Results: sTREM2 levels in serum and CSF were significantly elevated in PACNS patients and significantly associated with the mRS, NIHSS and ADL scores as well as inflammatory cytokine levels. Additionally, positive correlations were observed between the cerebral lesion volume and the sTREM2 levels in both blood and CSF. Higher sTREM2 levels in either the blood or CSF seemed to predict a good prognosis in PACNS patients. Conclusions: Our results indicate an association between serum and CSF sTREM2 levels and the severity of neurological damage. Thus, sTREM2 represents a potential biomarker for monitoring disease and potentially predicting the prognosis of PACNS patients.